Efektivitas Penggunaan Media Pembelajaran pada Mata Pelajaran PAI di SMA Darussalam Medan - Natasya, Samira; Tambunan, Nurhalima; Siregar, Bahtiar (Medan Resource Center, 2026)
This study aims to analyze the effectiveness of instructional media use in Islamic Religious Education (PAI) subjects at SMA Darussalam Medan. This research employed a qualitative descriptive approach with a case study design involving teachers and students as research participants. Data were collected through classroom observations, interviews with teachers and students, and documentation analysis. The data sources consisted of primary and secondary data, which were analyzed using data reduction, data display, and conclusion-drawing techniques. The findings indicate that the use of instructional media significantly improved students’ learning motivation, classroom participation, and understanding of abstract PAI concepts. The instructional media implemented included graphic media and projection media, which supported a more interactive, engaging, and student-centered learning process. These findings suggest that the integration of appropriate instructional media contributes positively to the effectiveness of Islamic Religious Education learning and can serve as a practical reference for teachers in improving classroom instruction.